Pengaruh Penerapan E-Billing dan E-Filling Terhadap Kepatuhan Wajib Pajak Dengan Pemahaman Perpajakan Sebagai Variabel Moderating - Hanum, Zulia; Muhammad Ikhwan Mulyawan (Politeknik Ganesha Medan, 2024)
The general aim of this research is to understand the impact of implementing E-Billing and E-Filing systems on taxpayer compliance, with taxation understanding as a moderating variable, among individual taxpayers. The study involves a sample of 217.725 individuals, with 100 taxpayers selected as participants from the tax object population. The research methodology employed is an Associative approach, focusing on exploring relationships or influences among variables. Data collection is conducted through questionnaires, consisting of written questions presented to respondents to measure their attitudes, opinions, and perceptions regarding social phenomena. Data analysis is including tests for data quality, classical assumption tests, multiple linear regression, and model feasibility tests involving 100 individual taxpayers. The results of this study indicate that the E-Billing system does not have a significant impact on taxpayer compliance, with a significance value of 0.002 < 0.05 and a t-value of 1.159 < 1.984. Conversely, the E-Filing system significantly influences taxpayer compliance, with a significance value of 0.000 < 0.05 and a t-value of 5.316 > 1.984. Collectively, the implementation of the E-Billing and E-Filing systems has a significant impact on taxpayer compliance, with a significance value of 0.000 < 0.05 and an F-value of 20.714 > 3.09. Respondents' perceptions regarding the taxation understanding variable strengthen the relationship between the implementation of the E-Billing and E-Filing systems and taxpayer compliance.